WEBSITE DESIGN TO SUPPORT LEARNING SYSTEM IN PRIVATE SD PUTRI DELI NAMORAMBE - Penda Sudarto Hasugian; Jijon Raphita Sagala (Sean Institute, 2022)
Education is a process of communication and information from educators to students which contains information about education, which has elements of educators as sources of information, media as a means of presenting ideas, ideas and educational materials as well as students themselves, some elements of This approach gets a touch of information technology media, thus sparking the birth of the idea of ​​e-learning. Deli Namorambe Putri Private Elementary School is still carrying out the direct learning process, where the entire teaching and learning process between teachers and students can only be done with class meetings. If there is no meeting between students and teachers in the classroom, the learning process will not occur. This causes the delivery of material and assignments to be disrupted so that it can result in a lack of student understanding of a learning material. The development of this system uses the PHP programming language, xampp as a local web server on the computer. With this system, it can help teachers and students in the teaching and learning process so that it can be used to fill out attendance lists, upload teaching materials, download teaching materials, take quizzes, send assignments and exams.